Analisis Kesejahteraan Karyawan Pada Kantor Pusat Dirjen Jenderal Pajak Jakarta Selatan - Andre Fuad Gunawan; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Universitas Katolik Widya Karya Malang, 2024)
Abstract. This research aims to determine the analysis of employee welfare at the Head Office of the Director General of Taxes, South Jakarta. This research uses a descriptive approach, namely by describing and analyzing the problems found. This qualitative research was obtained by observation, interviews and documentation. Meanwhile, secondary data was obtained through books, previous research and articles related to research. From the results of this research, it can be seen that the South Jakarta tax head office has carried out all existing management stages or cycles, but not all welfare in the prosperous life cycle has been well maintained. This can be seen from the extensive work and information system changes carried out by tax office employees.